319 A NOVEL NEURONAL SURVIVAL PATHWAY IN THE DEVELOPING CORTEX. (1st January 2005) - Genetta, T.; Wen, T. C.; Rogido, M.; Sola, A.
Abstract : Background: Hypoxic insult to the developing brain results in neuronal and glial cellular loss, in large part through apoptosis. A clearer understanding of the signaling pathways and downstream targets that these cells trigger to survive such insult is critical to the eventual development of therapeutic interventions to mitigate permanent neurological damage. We have discovered that a transcriptional repressor of the pro-apoptotic p73 gene, called ZEB (Zinc finger, E-box-binding factor), is itself up-regulated in response to hypoxic insult in the developing brain. Objective: To determine the mechanistic basis for the up-regulation of ZEB, as well as the functional consequences of this effect with regard to neuronal survival. Methods: Dominant negative versions of ZEB (that activate rather than repress) were constructed via standard recombinant DNA methodologies and transfected into primary cortical neurons isolated from E16 rat embryos. Additionally, P7 rat pups were subjected to unilateral focal cerebral ischemia via permanent occlusion of the mid cerebral artery (the contralateral side serving as control). At specific time points, brains were processed for and immunostained using antibodies against ZEB and the neuronal-specific antigen, NeuN. TUNEL staining was carried out using a standard kit protocol. Expression vectors encoding cDNAs for HIF-1 and dominant negative HIF-1 were obtained from the ATCC. Results: Dominant negative versions of ZEB causes primary cortical neurons to apoptose. In response to focal ischemic insult, ZEB protein was up-regulated in the nuclei of cortical neurons on the ischemic side. This increased expression is co-localized with an up-regulation of the EPO receptor on these neurons. At 12 and 24 Hr Post-FCI, ZEB-positive cells are mutually exclusive from TUNEL-positive cells (an end point indicator of cell death). Overexpressed HIF-1 alpha in normoxia up-regulates ZEB about 3-fold via ZEB-promoter-driven reporter analysis; overexpressing a dominant negative version of HIF-1 in primary neurons fails to up-regulate ZEB (via cytostaining). Conclusions: This is the first step in the elucidation of what may be a novel pro-survival pathway in the developing brain, one that is utilized by neurons to defend against proapoptotic insults, such as hypoxia. One well-characterized target of ZEB transcriptional repression, the p73 gene, encodes a protein that, in its full-length form, is known to play a role in neuronal cell death. Taken together, the above data suggest a potential link between pro-survival HIF-1 signaling and repression of the pro-death p73 gene and offer a potential mechanistic explanation for how a particular neuron might survive an ischemic insult.